A new compound in kidney stones? Powder X‐ray diffraction study of calcium glycinate trihydrate. (19th June 2013) - Le Bail, Armel; Daudon, Michel; Bazin, Dominique
<x xml:space="preserve">Abstract</x> The present identification of a new compound in kidney stones is relevant in clinical practice. Here, poly[[di‐μ‐aqua‐bis(glycinato‐κ2N, O)calcium(II)] monohydrate], {[Ca(C2H4NO2)2(H2O)2]·H2O}n, has been identified in a possible kidney concretion, although it could be a `false calculus' associated with Munchausen syndrome. The crystal packing is characterized by an infinite zigzag chain of Ca atoms in [Ca(OW)4O2N2] (OW is a water O atom) square antiprisms, sharing edges formed by water molecules. An uncoordinated water molecule interconnects the parallel chains in a three‐dimensional hydrogen‐bonding scheme. Similarities between the trihydrate and the monohydrate are described.